2021
DOI: 10.3390/vaccines9090961
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Preventive RSV Monoclonal Antibodies to Infants in Low- and Middle-Income Countries: Challenges and Opportunities

Abstract: Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory tract infections (LRTIs) in infants. Most deaths occur in infants under 3 months old, and those living in low and middle-income countries (LMICs). There are no maternal or infant RSV vaccines currently approved. An RSV monoclonal antibody (mAb) could fill the gap until vaccines are available. It could also be used when a vaccine is not given, or when there is insufficient time to vaccinate and generate an antibody response. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…A phase 3 trial of nirsevimab, an extended half-life mAb, showed 74.5% protection against RSV LRTI [36], slightly outperforming the Preferred Product Characteristics. However, this product has an anticipated price point suitable for high-income countries, and effectiveness of the biosimilar products under development may differ [9]. Third, our static model did not account for potential herd immunity effects of RSV LRTI prevention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A phase 3 trial of nirsevimab, an extended half-life mAb, showed 74.5% protection against RSV LRTI [36], slightly outperforming the Preferred Product Characteristics. However, this product has an anticipated price point suitable for high-income countries, and effectiveness of the biosimilar products under development may differ [9]. Third, our static model did not account for potential herd immunity effects of RSV LRTI prevention.…”
Section: Discussionmentioning
confidence: 99%
“…This increases logistic complexity and costs compared to the single-dose regimens expected for maternal vaccines and extended half-life mAbs. Finally, RSV vaccines may have lower efficacy during the first six months of life due to immune immaturity and interference from circulating maternal antibodies [9,12], a period coinciding with the highest RSV LRTI burden [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palivizumab provided the proof of concept that mAbs can be used to prevent RSV disease, and there are ongoing efforts to produce mAbs that provide a more sustained protective effect against RSV than licenced mAbs ( 67 , 68 ). As such, several long-acting mAbs are in clinical development for RSV prophylaxis in infants, including at least four mAbs in early development and two in late-stage development (nirsevimab and MK-1654) ( 56 ).…”
Section: Which Immunization Strategies Could Be Implemented To Protec...mentioning
confidence: 99%
“…Similar information is also not available for the other two mAbs in clinical development. Sponsors of all three mAbs have acknowledged the global burden of RSV, and the preponderance of RSV mortality in LMICs [6] .…”
Section: Long-acting Rsv Mabs Under Developmentmentioning
confidence: 99%